Feasibility of a Short-Term Virtual Reality Balance Intervention to Improve Mobility Smoothness in Parkinson's Disease - Schuch, Clarissa Pedrini; Balbinot, Gustavo; Bonilla, Marilley Nohely; Guedes Machado, Andréa; Oliveira, Alcyr Alves de (Frontiers in Virtual Reality, 2020)
Parkinson's disease (PD) is a neurodegenerative condition that is often associated with movement impairments, such as reduced balance and gait control. Virtual reality (VR) is a promising intervention for enhancing rehabilitation efficiency and may assist in overcoming functional limitations imposed by the disability. The objective of this study was to evaluate the feasibility, safety, and efficacy of a 5-weeks VR intervention in increasing mobility smoothness in participants with PD. Participants were assessed using functional mobility tasks—Timed Up and Go (TUG) and 10-m walking test (10MWT) and cognitive function tests. A total of 23 participants with a diagnosis of PD were randomly assigned to groups of VR or control interventions. In the VR group, for each session, participants received a VR-based balance training, i.e., tightrope simulator, for 20 min, preceded by 8 min of total body warm-up (total of 10 sessions over 5 weeks). Participants in the control group received 20 min of psychoeducation without a structured exercise program (twice a week). All screened participants engaged and completed a total of 10 VR-based intervention sessions. VR-based balance training caused no significant improvement in mobility smoothness for TUG or 10MWT (p > 0.05). Similarly, cognitive function was not affected by the VR intervention (p > 0.05). The outcomes of this study suggest that 10–20 min of VR-based intervention is a feasible and safe rehabilitation activity. However, it was insufficient to promote improvement in mobility smoothness and cognitive function in participants with PD. A combination of task-specific training in the virtual and physical environments in a more intensive approach is warranted for future study designs.